TEACHING MORAL VALUES THROUGH EYL LITERATURE: HOW? - Husnaini Husna (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
Abstract: Nowadays, teaching moral values is an obligation for every teacher in Indonesia. One of the ways to promote the moral values to young learners is through literature. As one of the literacy skills, reading skill must be prioritized as early as possible. English teacher as the agent of change can teach the moral values at the same time with teaching English, especially in teaching reading. Applying appropriate strategies and using relevant EYL literatures are assumed as the most effective methods to teach English and core moral values in the classroom. This paper will highlight theoretically the concept of moral value, the concept of good character, and the various strategies and activities to promote the core moral values through EYL literature. Keywords: character education, literature, moral values, teaching, TEYL